EIB Working Paper 2021/07 - Can European businesses achieve productivity gains from investments in energy efficiency? - Niczyporuk, Hanna (European Investment Bank, 2021)
When they consider investing in energy efficiency measures many firms focus only on direct energy savings and do not consider non-energy benefits that include increased labour productivity. To date, due to lack of high-quality data, few studies have attempted to quantify the effects of energy efficiency investments on firm-level outcomes other than reductions in energy consumption. This paper overcomes this barrier by using novel data from the EIB Investment survey of firms in the EU and the United Kingdom for the years 2018-2019. It studies the relationship between the energy efficiency investment and the labour productivity of European firms, utilising an instrumental variables methodology to account for potential endogeneity. The results show a positive and causal relationship between energy efficiency investment and labour productivity. The findings of the paper suggest that firms can benefit much more from the energy efficiency investment than what is often assumed, and highlight a need for government policies that would increase firms' awareness of these non-energy benefits.